Media Demonstration of Fiqh Learning on Unclean Material in Schools - Abdul Hafiz Baidawi; Zainudin Zainudin (Sustainable, 2023)
This study aims to develop a teaching aid media that is effective in helping students understand the concept of unclean in the school environment. This material is an important part of Islamic religious lessons, and the use of teaching aids is expected to improve students' understanding more interactively and interestingly. This study uses a qualitative approach and the type of Library Research (Library Research). Primary data sources were obtained through reference books that have been processed from books on visual media as well as journals, articles, and some references to the Fiqh unclean. Secondary data sources are obtained through Journal books, articles, and websites that support the discussion under study. The results showed that the use of teaching aids contributed to the development of fish learning methods that are more interactive and oriented to understanding concepts, especially in dealing with complex materials such as unclean ones.